KEPUASAN PESERTA DIDIK TERHADAP BIMBINGAN BELAJAR DI SEKOLAH MENENGAH PERTAMA NEGERI 04 SUNGAI RAYA - Marwah, Siti Muthiah; Purwanti, Purwanti; Yuline, Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe studentsâ€™ satisfaction is a reaction of feeling toward the experience acquired in the school with their expectation. Therefore, the students will satisfy if their perception toward the work of the BK teacher in giving his/her service could fulfil the studentsâ€™ expectation, the students then will satisfy with the study guidance given in the school. This research aims to know the studentsâ€™ satisfaction of VIII grade of SMP N 4 Sungai Raya toward the study guidance given by the teacher guidance and counseling, whether runs based on the studentsâ€™ expectation. The methodology of this research is descriptive method with the quantitative approach with the study of survey form. Sample of this research were 40 students. The data analysis result shows that the studentsâ€™ satisfaction level toward the study guidance is categorized â€œSatisfy Enoughâ€ with the percentage of 66,41 %. Based on the result above, it can be concluded that some students of VIII grade of SMP N 4 Sungai Raya were satisfied enough with the study guidance and some of them were not satisfied with the study guidance given by the school.Keywords: Studentâ€™s Satisfaction, Study Guidance